Knowledge of Junior High School teachers upon adolescent reproductive health in Yogyakarta Municipality - Ratni Indrawanti Ratni Indrawanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Objective: The aim of this study was to know the knowledge of Junior High School teacher upon adolescent reproductive health and the influencing factors.Materials and Methods: The study population is the teachers of Junior High Schools in Yogyakarta Municipality, 280 teachers were enrolled. Data on the characteristics and the knowledge upon the adolescent reproductive health were collected by questionnaire.Results: The teachers knowledge on the maturation of the female reproductive showed a statistical difference between the teacher group involved in the reproductive health teaching and the univolved group (p = 0.0004); the knowledge on the maturation of the male reproduction showed a statistical difference between the teacher group who had been in charge for more than 20 years compared to less than 20 year teacher (p = 0.015), likewise between the teacher group involved in the reproductive health teaching compared to the uninvolved (p = 0.0005); on the woman fertile period only 50% of the teachers had correct knowledge and there was a statistical difference between the teacher group involved in the reproductive health teaching and uninvolved group (p = 0.035). The score of the teacher's knowledge that a woman can become pregnant by a single sexual intercouse was inadequate (about 60% of full score) and there was a statistical difference between teacher group involved in the reproductive health teaching and the uninvolved group (p = 0.035); the score of the teacher's knowledge that a woman can become pregnant by interrupted sexual intercouse was inadequate (about 50% of full score) and there was a statistical difference between female and male teachers (p = 0.01), between the teacher group who had been in charge for more than 20 years compared to less than 20 year group (p=0.025). The teacher's knowledge that woman cannot become pregnant by vaginal rinsing soon after a sexual intercouse was inadequate (about 60% of full score) and the teacher group involved in the Religion, Biology and Physical Health teaching was less than the other group and there was a statistical difference (p = 0.037), likewise between the teacher group who had been in charge for more than 20 years compared to less than 20 year group (p = 0.019), between teacher group involved in the reproductive health teaching and the uninvolved group there was a statistical (p = 0.005). Concerning the knowledge on Herpes infection there was a statistical difference between teacher group involved in the reproductive health teaching and the uninvolved group (p = 0.007); concerning the teacher's behaviour on reproductive discussion with the students, the teachers involved in of Religion, Biology and Physical Health teaching or involved in guidance and councelling performed discussion more frequently compared to the other groups and a statistical differences was found (p= 0.00005). It was questionable that 64.8% teachers who were involved in the reproductive health teaching never discussed about the matter with their students. The teacher's knowledge on some diseases that can be transmitted by sexual activities was variable: on AIDS and Syphillis nearly 70% teachers knew, on Chlamydia 39.8% and on Herpes less than 15%. Logistic regression analysis to find the influencing factor on the teacher's knowledge showed: the involvement in the reproductive health teaching had influence on the knowledge upon the maturation of female and male sexual development more than the length of teaching, it influenced also the behavior to discuss sexual matter to the students. Gender and length of teaching did not influence the teacher's knowledge whether a woman can become pregnant by interupted sexual intercouse; the subject of teaching and the involvement that a woman will not become pregnant by rinsing their sexual organ soon after a sexual intercouse.Conclusion: The knowledge and behaviour or the Junior High School teacher's in Yogyakarta were inad- equate on some important issues and influenced especially by the subject teaching.Key word : adolescent reproductive health knowledge - Junior High School Teacher - influencing factors